Left atrial compression with acute heart failure caused by esophageal bolus. Issue 4 (27th June 2017) - Maffè, Stefano; Paino, Anna Maria; Paffoni, Paola; Bergamasco, Luca; Dellavesa, Pierfranco; Zenone, Franco; Cucchi, Lorenzo; Baduena, Lara; Franchetti Pardo, Nicolò; Parravicini, Umberto
ABSTRACT: We report a case of left atrial extrinsic compression caused by an esophageal food bolus in a patient presenting with acute heart failure. Transthoracic echocardiography along with contrast‐enhanced CT showed evidence of esophageal dilation producing left atrial compression. Esophageal endoscopy and fragmentation of the bolus, allowing the accumulated food to descend into the stomach, produced a rapid improvement of hemodynamic and clinical status. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 46 :259–261, 2018